Hydropower Potential at Simly Dam Site, Islamabad, Pakistan: Technical and Economic Review - Nazir, A.; Ajwad, A.; Jaffar, S.T.A.; Zahid, M.B.; Haider, S.M. (The Nucleus, 2022)
Renewable forms of energy are the most widespread focus these days, specifically the use of multiple options for generating alternate resources of energy. Hydropower is the best option known in terms of available renewable energy sources. In Pakistan, hydropower potential is immense, particularly in its existing Indus basin water resources systems. Since going for large hydropower developments is pretty costly and takes a lot of years, therefore, it would be advantageous if small hydropower plants are constructed on various locations having substantial hydropower potential. In this study, the hydropower potential at Simly dam site was investigated firstly for the run of the river scenario and secondly for the flows going to the filtration plant, based on the data for years 2016-20. It was found that in run of the river case, with the availability of 71 m head and 4.78 m3/sec inflow, 2.57 MW power can be generated from this small hydropower development. Similarly, for the second scenario, 0.87 MW power can be produced by utilizing the hydraulic energy of water going towards the filtration plant. When the benefit cost ratio was estimated, the run of the river case was found more suitable with ratio of 1.4. Consequently, it was understood that this small addition to hydropower can help to fulfill 1/6 part of power demand of people living in Islamabad.